Evaluation of mechanichal properties of polymer composite material - Abdul Rahim Kamaruddin (2023)
This research studied the mechanical properties of the denture base composite when Zirconia (ZrO2) nanoparticles filler added to polymethyl methacrylate (PMMA) denture base. ZrO2 was surface treated with 3-methacryloxypropyl (trimethoxysilane, γ-MPS), then incorporated with methyl methacrylate (MMA), and mixed with PMMA powder. The volume fraction of the filler in the nanocomposites were 0.5, 1.0, 2.0 and 4.0 wt.%. The effect of the filler capacity on mechanical properties was studied using hardness, tensile strength and impact strength test. The hardness was determined through Rockwell hardness test method. Moreover, the tensile test was done by using universal testing machine with pre-set standard ASTM D638. Furthermore, the impact resistance of the material was evaluated by calculating the Charpy Impact Value. Nanocomposite with 0.5 wt.% of filler content has the highest tensile strength, tensile force and hardness when compared to other which were at 29.15 MPa, 699.6 N and 14.4 HRB respectively. Besides that, nanocomposite with filler content of 1.0 wt.% has the highest Charpy Impact Value which was 7000 J/m2. It was recommended for the upcoming future researcher to conduct morphology test, water absorption test, water solubility test and thermal stability test when evaluating the effect of micro or nano fillers on the enhancement of mechanical properties of denture base resin.